2023
DOI: 10.1002/adhm.202203056
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Injectable Hydrogel Sequentially Delivers AntagomiR‐467a‐3p‐Loaded and AntagomiR‐874‐5p‐Loaded Satellite‐Cell‐Targeting Bioengineered Extracellular Vesicles Attenuating Sarcopenia

Abstract: Sarcopenia is a geriatric disease characterized by reduced muscle function and mass. The capacity to self-renew and myogenesis of satellite cells (SCs) declines with age, resulting in age-related sarcopenia. MicroRNAs (miRNAs) can regulate the proliferation and myogenesis of SCs. In this study, it is identified that miR-467a-3p and miR-874-5p could respectively mediate the stemness and myogenesis of SCs by performing bioinformatics analysis. AntagomiR-467a-3p (ant-467a) and antagomiR-874-5p (ant-874) improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Some miRNAs, such as miR-1 [ 171 ] and miR-133 [ 172 ], have been shown to play an important role in promoting muscle regeneration, while other miRNAs are pathogenic to muscle wasting, such as miR-29b [ 173 ] and miR-628 [ 174 ]. Xu et al [ 175 ] showed that miR-467a-3p and miR-874-5p inhibited the differentiation of SCs and the formation of muscle tissue, respectively. They overexpressed TSG101 to target SCs on the BMSCs-EVs surface, and transported antagomiR-467a-3p and antagomiR-874-5p, respectively, to construct two engineered EVs.…”
Section: The Application Of Evs-loaded Hydrogels In Disease Treatmentmentioning
confidence: 99%
“…Some miRNAs, such as miR-1 [ 171 ] and miR-133 [ 172 ], have been shown to play an important role in promoting muscle regeneration, while other miRNAs are pathogenic to muscle wasting, such as miR-29b [ 173 ] and miR-628 [ 174 ]. Xu et al [ 175 ] showed that miR-467a-3p and miR-874-5p inhibited the differentiation of SCs and the formation of muscle tissue, respectively. They overexpressed TSG101 to target SCs on the BMSCs-EVs surface, and transported antagomiR-467a-3p and antagomiR-874-5p, respectively, to construct two engineered EVs.…”
Section: The Application Of Evs-loaded Hydrogels In Disease Treatmentmentioning
confidence: 99%